Planning and design of information systems - Blokdijk, Andre (Academic, 1991)
Planning and Design of Information Systems provides a theoretical base and a practical method of executing the planning of computerized information systems, and the planning and design of individual applications. The book is organized into five parts, covering the non-technical and nonimplementational part of information systems planning, design, and development. Part I gives the theoretical base for the subsequent parts of the book. It discusses modeling, techniques, notations, boundaries, quality issues and aspects, and decomposition techniques and problems. Part II discusses the needs, problems, and possible solutions for user participation. It describes user organizations, in respect of culture; maturity in the use of automation and computers; and gives a synthesis of participation, cultures, maturity, and information systems development techniques. Part III describes how to develop an Information Systems Architecture, an Information Systems Plan, and a Data Architecture. Part IV presents a structured, programmed approach to planning an application in a short period while maintaining high quality, and discusses project management of application development. Part V covers information analysis, data specification and conceptual data base design, and process and dialog design.